2019
DOI: 10.1186/s13018-019-1280-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the formation of double-contour sign and tophi in gout

Abstract: Background This study aimed to confirm the diagnostic accuracy of ultrasound (US) on gout and explore the potential risk factors for double-contour sign and tophi formation in gout patients. Methods The US analyses were performed on all knee, ankle, and first metatarsophalangeal (MTP 1) joints to reveal the type and location of lesions. While a questionnaire and blood biochemical index were used to explore the potential risk factors for double-contour sign and tophi in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Previous studies have shown that age, duration of gout, and eGFR are risk factors for the development of US‐detected tophi and multiple subcutaneous tophi (36–38). This is consistent with our own finding of an association between age and duration of gout with the development of tophi, which remained significant after multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that age, duration of gout, and eGFR are risk factors for the development of US‐detected tophi and multiple subcutaneous tophi (36–38). This is consistent with our own finding of an association between age and duration of gout with the development of tophi, which remained significant after multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…If the blood creatinine value is higher than the normal value, it indicates kidney damage; therefore, the blood CREA level can more accurately reflect renal parenchymal damage. 27,28 Our research found that the higher the CREA level, the higher the risk of renal cortex thinning in gout patients, suggesting that in the clinical diagnosis and treatment process, we could indirectly predict renal function impairment through the US changes in the renal cortex. In contrast, we could also use the blood CREA level to predict the related changes in the renal cortex indirectly.…”
Section: Discussionmentioning
confidence: 77%
“…Deposition of monosodium urate crystals on the most superficial layer of hyaline cartilage results in "double contour sign" which is an irregular echogenic line demonstrated on ultrasonography and notably manifests during gout flare-up in patients with a prior history of gout attacks, and with asymptomatic hyperuricemia [5]. However, the sensitivity of these findings on ultrasonography ranges between 25% and 95% [6].…”
Section: Discussionmentioning
confidence: 99%